Experiences of Living with Severe Chronic Fatigue Syndrome/Myalgic Encephalomyelitis - Strassheim, Victoria (Healthcare (Basel), 2021)
Chronic Fatigue Syndrome/Myalgic Encephalomyelitis (CFS/ME) is a rare disease with no known etiology. It affects 0.4% of the population, 25% of which experience the severe and very severe categories; these are defined as being wheelchair-, house-, and bed-bound. Currently, the absence of biomarkers necessitates a diagnosis by exclusion, which can create stigma around the illness. Very little research has been conducted with the partly defined severe and very severe categories of CFS/ME. This is in part because the significant health burdens experienced by these people create difficulties engaging in research and healthcare provision as it is currently delivered. This qualitative study explores the experiences of five individuals living with CFS/ME in its most severe form through semi-structured interviews. A six-phase themed analysis was performed using interview transcripts, which included identifying, analysing, and reporting patterns amongst the interviews. Inductive analysis was performed, coding the data without trying to fit it into a pre-existing framework or pre-conception, allowing the personal experiences of the five individuals to be expressed freely. Overarching themes of ‘Lived Experience’, ‘Challenges to daily life’, and ‘Management of the condition’ were identified. These themes highlight factors that place people at greater risk of experiencing the more severe presentation of CFS/ME. It is hoped that these insights will allow research and clinical communities to engage more effectively with the severely affected CFS/ME population.